The Protective Effect of 3-O-Acetyl-11-Keto-Beta Boswellic Acid-Nanostructured Lipid Carriers and Magnesium Oxide Nanoparticles on Experimental Liver Fibrosis - Alsamkari, Afraa; Abd El-Aziz, Gamal Said; Hindi, Emad Ahmed; Aly Ahmed , Osama Abdelhakim (Journal of Contemporary Medical Sciences, 2025)
Objectives: Chronic liver disease is a massive burden that causes 2 million deaths, annually. No FDA-approved treatment exists. This study aimed to compare 3-Acetyl-11-Keto-Beta-Boswellic Acid (AKBA), Magnesium Oxide Nanoparticles (MgO NPs), and AKBA-Nanostructured Lipid Carriers (NLCs) combined with MgO NPs (AKBA-NLC + MgO NPs) in the treatment of thioacetamide (TAA)-induced liver fibrosis in rat model. Methods: The AKBA-NLCs were prepared using high-sheer homogenization emulsification and sonication method and characterized using DLS and TEM. Twenty-five Wistar male rats (n = 25) were assigned randomly into five groups: Group 1: negative control group receives 1 ml of distilled water via i.p. (intraperitoneal injection), 3 times weekly for 4 weeks and 1 ml of distilled water p.o. (by oral gavage). Group 2: TAA model (200 mg/kg body weight (b.wt.), i.p.), 3 times per week for 4 weeks. Group 3: TAA + MgO NPs (100 μg/ml, p.o.). Group 4: TAA + AKBA (10 mg/kg b.wt., p.o.). Group 5: TAA + (AKBA-NLC 10 mg/kg b.wt. + 100 μg/ml MgO NPs p.o.). All groups, except Group 1, received the same dosage of thioacetamide as received by Group 2. All groups, except group 2, received their corresponding oral treatments/vehicle daily for 4 weeks. Liver injury was assessed via serum biomarkers (ALT, AST, albumin, bilirubin), tissue cytokines (TNF-α, IL-1β, IL-6, GSH), histopathology (H&E, Masson’s Trichrome), and α-SMA immunohistochemistry. One-way analysis of variance (ANOVA) and the Tukey–Kramer tests were used for analyzing data statistically and (p < 0.05) was considered statistically significant. Results: serum liver function, inflammatory and oxidative stress markers were comparably reduced in all treatment groups, but collagen deposition and α-SMA expression were significantly lower in the combination group. Conclusion: This dual nanomedicine approach warrants further investigation as a therapeutic strategy for hepatic fibrosis.